Educational Inequality and Economic Mobility in Bangladesh: A Socioeconomic Analysis - Buddha Dev Biswas (Britain International for Academic Research (BIAR) Publisher, 2025)
Education plays a pivotal role in personal advancement and national economic development, serving as a key driver of social and economic mobility. Although Bangladesh has made notable progress in expanding access to education, significant inequalities persist across geographical regions, gender groups, and socioeconomic classes. These disparities limit access to quality education and constrain upward economic mobility, particularly among marginalized communities. The paper examines the multifaceted relationship between educational inequality and economic mobility in Bangladesh using secondary data and thematic analysis. The findings highlight several crucial determinants such as the rural-urban divide, gender-based disparities, and socioeconomic barriers that continue to impede equitable access to education. These structural challenges perpetuate cycles of poverty, restrict labor market opportunities, and hinder national productivity. The study underscores the urgent need for comprehensive policy reforms, equitable resource distribution, and inclusive educational initiatives to reduce educational disparities and foster a more just and sustainable economic future for Bangladesh.